From Entrepreneurship Education, Government Support, and Global Competence to Entrepreneurial Behavior: The Serial Double Mediating Effect of the Self-Efficacy and Entrepreneurial Intention - Zhang, Jinzi; Li, Bing; Zhang, Yanning; Gong, Chi; Liu, Ziyang (Frontiers in Psychology, 2022)
Entrepreneurship plays a significant role in promoting the social and economic development of a country. At present, entrepreneurship education is widely carried out in universities and colleges in order to improve students’ entrepreneurial ability, and then to provide support for the formation of a comprehensive entrepreneurial situation. As entrepreneurship education has gradually become a hot topic of teaching for innovation and entrepreneurship education of international students, studies on the influencing mechanism of entrepreneurship education of international students in relation to their entrepreneurial behavior are conducive to providing theoretical basis and empirical evidence for international students’ entrepreneurship education, so as to pertinently guide international students’ innovation and entrepreneurship practice. This study aims to explore the influence of entrepreneurship education, government support for entrepreneurship, global competence, entrepreneurial self-efficacy and entrepreneurial intention on the entrepreneurial behavior of international students in the Republic of Korea (“Korea”). It summarized and drew on the results of the existing literature research. According to the contents and points of research, this study takes the international students studying in Korea as the sample and uses statistical analysis software, SPSS 22.0 and AMOS 24.0, to establish a structural equation model to conduct empirical study on the influencing mechanism of entrepreneurial behavior of international students in Korea, so as to better understand the influence of entrepreneurship education in Korean universities and colleges on entrepreneurial behavior of international students in Korea. Based on the analysis results, this study puts forward the theoretical basis for the policies related to effective management of entrepreneurship, which will help alleviate the unemployment of young people studying in Korea and the tight labor market supply and demand.